2017
DOI: 10.1111/vox.12558
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of transfusion‐associated graft‐versus‐host disease with pathogen‐reduced platelets with amotosalen and ultraviolet A light: a review

Abstract: Background and Objectives Transfusion-associated graft-versus-host disease (TA-GVHD) is a serious complication of blood component transfusion therapy, caused by donor T lymphocytes. c-Irradiation or pathogen inactivation methods, capable of inactivating proliferating T cells in blood components, should be selected to prevent TA-GVHD. This review summarizes the published evidence to support the use of pathogen-reduced platelets with amotosalen (150 lM) and ultraviolet A light (UVA, 320-400 nm, 3 J/cm 2 ) for pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 34 publications
2
23
0
3
Order By: Relevance
“…Routine use of the technology since then has resulted in no reported cases of TA-GVHD associated with the transfusion of INTERCEPT-treated platelet (or plasma) components after transfusion of 400,000 components under direct observation through hemovigilance studies or national hemovigilance systems, and no reports to the manufacturer on the transfusion of more than 1.5 million components manufactured for transfusion since the approval of the system for use in lieu of gamma irradiation. 39 This experience was consistent with clinical and postmarketing trial experience where amotosalen/UVAtreated platelet components were used for patient populations at risk. 40,41 After consideration of the system routine performance and the data above, AABB standards have included the use of amotosalen/UVA as an alternative to gamma since 2015 in the United States.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Routine use of the technology since then has resulted in no reported cases of TA-GVHD associated with the transfusion of INTERCEPT-treated platelet (or plasma) components after transfusion of 400,000 components under direct observation through hemovigilance studies or national hemovigilance systems, and no reports to the manufacturer on the transfusion of more than 1.5 million components manufactured for transfusion since the approval of the system for use in lieu of gamma irradiation. 39 This experience was consistent with clinical and postmarketing trial experience where amotosalen/UVAtreated platelet components were used for patient populations at risk. 40,41 After consideration of the system routine performance and the data above, AABB standards have included the use of amotosalen/UVA as an alternative to gamma since 2015 in the United States.…”
Section: Discussionsupporting
confidence: 71%
“…37,38 Analysis in previously reported LDA studies showed effective inactivation of T cells to the LOD at more than 5.39 6 0.29 log, 25 and the inactivation of the T cells was further found to be below the LOD, even when the doses of the amotosalen and UVA were reduced by a combined 3000-fold, indicating that at least a 3000fold level of safety exists for the treatment of blood components for the complete inactivation of T cells. 25,30,39 An established parent-to-F1 mouse transfusion model of TA-GVHD was used to show that treatment of splenocytes with amotosalen/UVA prevents TA-GVHD, in a manner similar to a gamma irradiation treatment control and unlike the untreated positive control. 32 In the same study, inactivation of the T cells with amotosalen/ UVA showed inactivation by LDA to the LOD, establishing a correlation between prevention of clinical TA-GVHD and reduction of the T-cell viability below the LOD.…”
Section: Discussionmentioning
confidence: 99%
“…As the Amotosalen/UVA pathogen reduction method targets nucleated leukocytes, it is also effective at preventing transfusion‐related graft‐versus‐host disease . Therefore, Amotosalen/UVA‐treated PCs do not require gamma‐irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, irradiation is not required to prevent transfusion‐associated graft‐versus‐host disease (TA GVHD) for platelets that have undergone PR . However, for transfusion services that irradiate their own blood products, an irradiator would still be required for red blood cells.…”
Section: Resultsmentioning
confidence: 99%